2021
DOI: 10.1016/j.jvs.2020.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Vascular surgeon wellness and burnout: A report from the Society for Vascular Surgery Wellness Task Force

Abstract: Introduction: Physician burnout has been linked to medical errors, decreased patient satisfaction, and decreased career longevity. In light of the increasing prevalence of cardiovascular disease, vascular surgeon burnout presents a legitimate public health concern owing to the impact on the adequacy of the vascular surgery workforce. The aims of this study were to define the prevalence of burnout among practicing vascular surgeons and identify factors that contribute to burnout to facilitate future Society for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…55,56 A recent survey of SVS members at-large revealed that two out of five vascular surgeons report burnout, one in three report symptoms of depression in the past month, and 8% indicated they had considered suicide in the last year. 57 Among vascular trainees, more than 60% report at least one feature of distress on a weekly basis. 58 In a recent survey of vascular surgery trainees, one in ten were sexually harassed, and nearly two in five experienced discrimination on the basis of gender.…”
Section: Implications For Student and Physician Wellnessmentioning
confidence: 99%
“…55,56 A recent survey of SVS members at-large revealed that two out of five vascular surgeons report burnout, one in three report symptoms of depression in the past month, and 8% indicated they had considered suicide in the last year. 57 Among vascular trainees, more than 60% report at least one feature of distress on a weekly basis. 58 In a recent survey of vascular surgery trainees, one in ten were sexually harassed, and nearly two in five experienced discrimination on the basis of gender.…”
Section: Implications For Student and Physician Wellnessmentioning
confidence: 99%
“…Our results echo similar analyses among surgical subspecialists, advance practice nurses, and general internists that also point to clinical work hours and electronic medical record requirements as determinants of burnout. [33][34] While burnout was not explicitly mentioned in an earlier analysis among medical students and residents, respondents named a high clinical workload and poor work-life balance as deterrents to pursuing a nephrology fellowship. Thus, mitigating such factors associated with burnout as clinical work hours during training may be key to attracting prospective applicants to nephrology.…”
Section: Discussionmentioning
confidence: 96%
“…In its 2019 update, the Society for Vascular Surgery (SVS) Wellness Task Force study demonstrated that 41% of vascular surgeons met the criteria for burnout, 36% reported depression, and 8% reported thoughts of suicide in the previous month. 30 Although the SVS Wellness Task Force did not report an association between compensation or debt and burnout, it is reasonable to conclude that as the diversity within the field increases, the effects of debt and disparities in compensation will become more pronounced.…”
Section: Vascular Surgeon Personal Debt Perspectivementioning
confidence: 97%